Sensitivity of Real‐Time Forecast for Typhoons Around Korea to Cumulus and Cloud Microphysics Schemes. Issue 3 (7th February 2023) - Park, Jinyoung; Moon, Jihong; Cho, Woojin; Cha, Dong‐Hyun; Lee, Myong‐In; Chang, Eun‐Chul; Kim, Joowan; Park, Sang‐Hun; An, Jooneun
Abstract: In numerical weather prediction models, the typhoon track and intensity forecast performances are highly sensitive to physics parameterization schemes. To investigate the impact of physics parameterization schemes on the real‐time short‐term forecasts, we simulated six typhoons which directly/indirectly affected the South Korea region in recent years using the Weather Research and Forecasting (WRF) model. Three cumulus parameterization schemes (CPSs) of Kain‐Fritsch (KF), Betts‐Miller‐Janjić (BMJ), modified Tiedtke (TDK), and two cloud microphysics parameterization schemes (MPSs) of WRF‐single‐moment‐microphysics class 6 (WSM6), Predicted Particle Properties (P3) 1‐category were selected for the sensitivity experiment. The results showed that there was a significant difference in simulated typhoon track and intensity performances depending on the physics schemes. On average, the typhoon forecast performances were improved when applying the KF scheme for CPS and WSM6 scheme for MPS in our experimental setup. The BMJ‐applied runs showed the worst performances, which simulated westward shifted typhoon tracks compared to other runs. Overall, the typhoon track and intensity spreads tended to be more sensitive to CPSs and MPSs, respectively. We conducted additional sensitivity experiments using the BMJ scheme with modified reference and temperature profiles. The result showed that the overactivity of the BMJ scheme at low latitudes was reasonably reduced, leading to the improved simulation of typhoons and synoptic fields. Plain Language Summary: To improve the real‐time short‐term forecast performances for the recent typhoon cases that affected South Korea, sensitivity experiments for the various physics parameterization schemes, such as cumulus parameterization and cloud microphysics schemes, were conducted. Through additional experiments with one of the modified schemes and a comparison of detailed inner cloud processes, the reason for the different track and intensity forecast performances among the sensitivity experiments were revealed. Key Points: The effect of cumulus parameterization and cloud microphysics schemes on the real‐time forecast of typhoons around South Korea is studied One of the cumulus parameterization schemes was modified to decrease its activity at low latitudes Even short‐term typhoon forecasts could be largely affected by the forecast performances of convective processes at the tropics